Editorial (International Journal of Business Innovation, 2023)
Welcome to the latest edition of the International Journal of Business Innovation! As we embark on this journey of exploration and knowledge, we are thrilled to present a collection of groundbreaking research and insightful discoveries. This journal serves as a platform for the exchange of ideas, where experts from various fields converge to push the boundaries of scientific understanding. Our editorial team is proud to bring you a set of papers that showcase the remarkable achievements and advancements in their respective disciplines, namely Accounting, Finance, and Management. We invite you to join us on this intellectual adventure as we uncover the scientific world and strive to make a relevant impact on business innovation.The paper titled "Bibliometric Analysis of the Accounting Research in Intangible Capital Journal" lies in its aim to analyze the research in accounting published in the Intangible Capital Journal over the past twelve years. By examining past trends and identifying future research opportunities, the study provides valuable insights into the field of accounting. The fact that financial accounting is the most studied area, with a focus on the private sector and a quantitative research approach, highlights the current emphasis in this domain. Additionally, the study sheds light on the preferred data collection methods, such as document and content analysis. It's interesting to note the patterns of co-authorship, with works often featuring 2 or 3 authors and the significant presence of female authors from Spanish universities. This information helps to understand the research landscape and the countries most represented in the sample papers. Furthermore, the study highlights areas that are not yet adequately represented, such as public accounting and teaching/research in accounting, which could present future avenues for exploration. Overall, this article provides valuable insights and potential directions for further study in the field of accounting.This second article titled “Budgetary Control and Financial Performance of Manufacturing SMEs in Osun State, Nigeria: A Quantitative Approach” sounds relevant to the field of financial management in small and medium enterprises (SMEs). The study aims to determine the different types of budgets used by SMEs and assesses the influence of budgetary control on their financial performance in Osun State, Nigeria. By collecting data from 200 completed questionnaires, the study provides insights into the budgeting practices, budget control, and financial performance of these SMEs. The regression analysis conducted in the study reveals a significant influence of budgetary control on the financial performance of SMEs. This finding suggests that budget control is a powerful management tool that enables managers to carefully analyze their operations. By implementing effective budget control practices, SMEs can improve their financial performance and enhance their sustainability, even in a competitive global environment. The study provides a valuable recommendation for SMEs to organize seminars, workshops, and short courses on different types of budgets. This would help managers make more effective decisions aligned with the organization's desired performance in pursuing short-term goals. Such initiatives would further enhance the financial management practices of SMEs and contribute to their overall success.This article “Achieving Inclusive Fintech and Digital Financial Inclusion through Financial Capability” lies in its examination of the impact of financial capability on digital financial inclusion, specifically in the public sector of the Bono East Region in Ghana. By analyzing data from 1080 employees, the study utilizes econometric analysis to explore the relationship between financial capability and digital financial inclusion. This article's relevance is significant as it sheds light on the importance of financial capability in promoting digital financial inclusion. By highlighting the impact of various factors such as financial literacy, skills, attitude, and behavior, the study provides valuable insights for policymakers, organizations, and individuals looking to enhance digital financial inclusion efforts in the public sector of the Bono East Region in Ghana. These findings can inform the development of strategies, programs, and interventions aimed at fostering a more inclusive and financially empowered society. Overall, this article contributes to the understanding of the relationship between financial capability and digital financial inclusion, emphasizing the role of different factors in driving inclusion. It offers valuable insights that can be utilized to guide decision-making and initiatives in promoting digital financial inclusion in the region and potentially beyond.Finally, the article “Identification and Validation of the Maritime Cluster in Portugal: An Exploratory Analysis” is important for understanding the functioning and dynamics of the Maritime Cluster in Portugal. The study aims to analyze whether the Maritime Cluster in Portugal exhibits characteristics of a cluster and if it functions as one. The article also discusses the impact of European policies on cluster formation in Portugal. By utilizing geographical concentration indicators as a research methodology, the study concludes that the Maritime Cluster in Portugal fulfills the conditions of a cluster. This suggests that there is a significant geographical concentration of maritime activities in the selected NUTS III region. Furthermore, the study observes an increase in the specialization of the maritime cluster and notes its clear contribution and strengthening in the region under study and for the country. The relevance of this article lies in its exploration of the Maritime Cluster in Portugal. Understanding the characteristics and dynamics of this cluster is crucial for policymakers, industry players, and researchers interested in the maritime sector. The findings, which indicate the successful formation and functioning of the cluster, suggest that European policies supporting clusterization have had positive effects on the maritime sector in Portugal. Overall, this article helps to enhance our understanding of the Maritime Cluster in Portugal and highlights the benefits and positive impacts of cluster formation in the country. It provides valuable insights for policymakers and stakeholders in the maritime industry and contributes to the broader discussion on cluster development and its relationship with European policies.In conclusion, we invite all readers to appreciate the rich contributions presented in this issue of our journal. The diverse articles encompass a wide range of topics, shedding light on innovative research, breakthrough discoveries, and thought-provoking perspectives. We extend our gratitude to the authors who have shared their expertise and insights, contributing to the collective knowledge of our scholarly community.As we move forward, we encourage all readers to actively participate in the growth and success of International Journal of Business Innovation. Your contributions, whether through submitting research papers, sharing your expertise as a reviewer, or engaging in fruitful discussions, are invaluable in shaping the next issue. Your unique perspectives and experiences will enrich the dialogue and drive further advancements in our respective fields.We look forward to your active involvement and contributions in the next issue of our journal, as we strive to expand the frontiers of knowledge and make meaningful contributions to business innovation.Thank you for your unwavering support, and we eagerly await your continued involvement in the International Journal of Business Innovation.
Keywords: editorial